(untitled) (CIPEEX, 2025)
Street (or road) running is relatively understudied due to limitations of field-based measurements and the diverse heterogeneity of its practitioners. With regard to blood pressure, there are no published field-based studies comparing different training methodologies. The objective of this study is to evaluate subacute blood pressure (BP) responses in healthy young adults who practice street running after a high-intensity interval running session, a moderate-intensity continuous running session, and a control session. This is a cross-sectional study conducted with 10 street runners who underwent three protocols: Continuous Aerobic Protocol (CAP), High-Intensity Interval Training (HIIT), and Control Protocol (CP). Hemodynamic measurements were taken pre-exercise, immediately post-exercise, and every 10 minutes up to 40 minutes after each protocol. Results: Significant elevation of SBP immediately after the running session, in both CAP and HIIT versus the pre-exercise, however, it was observed a significant increase in the HIIT group. These responses were not excessive, returning to baseline values in the subsequent moments (without significant differences in intra- or inter-group analyses). Diastolic BP (DBP) increased significantly immediately post-exercise and at 20 minutes in both exercise protocols, immediately after exercising and 20 minutes later, but to the same extent, showing similar magnitude. At 40 minutes, the HIIT group maintained a significantly higher DBP than the CAP group. Conclusion: Runners exhibited higher BP (blood pressure) values immediately after both exercise sessions, with similar magnitude, but did not demonstrate post-exercise hypotension in either protocol.